Aspek Pendidikan Akhlak dalam Film Animasi Riko The Series - Surnita Surnita; Syafei Syafei (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to find out what aspects of akhlak education are contained in the animated film